Review of Thompsoniella Guimarães with description of a new species from Colombia (Diptera, Calliphoridae, Mesembrinellinae) (2014)
ABSTRACT: Review of Thompsoniella Guimarães with description of a new species from Colombia (Diptera, Calliphoridae, Mesembrinellinae). The Mesembrinellinae (Diptera, Calliphoridae) are exclusively Neotropical with nine genera comprising 36 recognized species, including the genus Thompsoniella Guimarães with a single species, T. anomala Guimarães. We describe a new species, Thompsoniella andina sp. nov., from the Departments of Antioquia and Caldas, Colombia (Cordillera Central of the Andes, between 2600 - 2700 m) and redescribe T. anomala. A key to the nine genera of Mesembrinellinae and a key to the males of the two species of Thompsoniella are provided. Color photographs to illustrate the two species of Thompsoniella and drawings of the male genitalia of both species are also provided. Here we record Thompsoniella for the first time in Colombia.